An encapsulation–reduction–catalysis confined all-in-one microcapsule for lithium–sulfur batteries displaying a high capacity and stable temperature tolerance. (14th May 2021) - Zhu, Mengfei; Yang, Chaoyu; Han, Tianli; Hu, Chaoquan; Wu, Yong; Si, Ting; Liu, Jinyun
Abstract : A novel all-in-one microcapsule is prepared by in situ growing carbon nanotubes inside a microcapsule using encapsulated cobalt oxide nanoboxes for Li–S batteries, which displays high energy-storage performance. Abstract : Developing emerging host materials for constructing high energy-density lithium–sulfur (Li–S) batteries has received extensive attention. Herein, we develop a carbon nanotube (CNT)/S-infilled all-in-one microcapsule for Li–S batteries by catalytically growing CNTs using reduced Co3 O4 nanoboxes inside a microcapsule. The encapsulation of Co3 O4 nanoboxes into the microcapsule is achieved by using an oil-in-water emulsion. In the all-in-one microcapsule, the CNTs improve the conductivity, the microcapsule shell reduces the loss of polysulfides during cycling, and the void inside the microcapsule efficiently accommodates the volumetric change of sulfur. A Li–S battery based on the all-in-one microcapsule exhibits a high capacity of 1010 mA h g −1 after 250 cycles and a coulombic efficiency of ≈99.8%. Moreover, the battery displays stable performance when cycling at temperatures of −5 °C and 45 °C, which indicates its good potential for practical applications.